Plant Regeneration via Somatic Embryogenesis in Mature Wild Olive Genotypes Resistant to the Defoliating Pathotype of Verticillium dahliae - Narváez, Isabel; Martín, Carmen; Jiménez-Díaz, Rafael M.; Mercado, Jose A.; Pliego-Alfaro, Fernando (Frontiers in Plant Science, 2019)
Regeneration capacity, via somatic embryogenesis, of four wild olive genotypes differing in their response to defoliating Verticillium dahliae (resistant genotypes StopVert, OutVert, Ac-18 and the susceptible one, Ac-15) has been evaluated. To induce somatic embryogenesis, methodologies previously used in wild or cultivated olive were used. Results revealed the importance of genotype, explant type and hormonal balance in the induction process. Use of apical buds obtained from micropropagated shoots following the methodology of Mazri et al. (2013) in cultivated olive (4 days induction in liquid medium supplemented with 30 µM TDZ – 0.54 µM NAA, followed by 8 weeks in basal 1/2 MS medium) was adequate to obtain somatic embryos in 2 genotypes, StopVert and Ac-18, with a 5.0 and 2.5% induction rates, respectively; however, no embryogenic response was observed in the other two genotypes. Embryogenic cultures were transferred to basal ECO medium supplemented with 0.5 µM 2iP, 0.44 µM BA and 0.25 µM IBA for further proliferation. Somatic embryos from StopVert were maturated and germinated achieving a 35.4% conversion rate. An analysis of genetic stability on StopVert, using SSRs and RAPDs markers, was carried out in embryogenic callus, plants regenerated from this callus and two controls, micropropagated shoots used as explant source and the original mother plant. Polymorphism was only observed in the banding pattern generated by RAPDs in one of the 10 callus samples evaluated, resulting in a variation rate of 0.07%. This is the first time in which plants have been regenerated via somatic embryogenesis in wild olive.